The warm-up maximize performance and improve long-term athletic development - Jeffreys, Ian (Human Kinetics, 2019)
The Warm-Up is the first book to describe the science of the warm-up and provide guidelines to maximize its effectiveness through the process of constructing effective RAMP-based warm-ups. The RAMP system-Raise, Activate, Mobilize, and Potentiate-looks at the warm-up not only as preparation for the upcoming session, but also as tool for athletic development that can cultivate the skills and movement capacities needed to excel in sport. RAMP has become a standard warm-up system recommended by the United Kingdom Strength and Conditioning Association (UKSCA) and is included in professional resources developed by the National Strength and Conditioning Association (NSCA). The Warm-Up provides a library of activities that can be used to maximize the effectiveness of warm-ups within the structure of the RAMP system. Coaches and athletes can incorporate activities to develop warm-ups that directly contribute to performance, or they can use one of five sample RAMP warm-up programs, which are appropriate for a variety of sports and athlete training levels. More than 160 diagrams and photos enhance the text and provide direction for the drills and exercises, and 17 video clips demonstrate movement patterns of the Raise phase. Plus, exercise and drill finders make it easy to find the exercises best suited for specific needs. It's time to make the warm-up part of the long-term athlete development plan. The Warm-Up will help coaches and athletes use the RAMP system to make warm-ups a more effective part of training that contributes to better performance.